Odpowiedzi

2009-12-11T21:32:54+01:00
1)(b+3)² - (b-3)² = b²+6b+9-b²+6b-9 = 12b
2)(5m+4n)² - (4m-5n)² =25m²+40mn+14n²-16m²+40mn-25n²=9m²+80mn-9n²
3)(3x-2)² + 2(x+3)² =9x²-12x+4+2x²+12x+18=11x²+22
4)(y²+1)² -2(y²-1)² =y⁴+2y²+1-2y⁴+2y²-2=-y⁴+2y²-1
5)(5-0,2k³)² + 5(k³-5) = 25-2k³+0,04k⁶+5k³-25=0,04k⁶+3k³
Najlepsza Odpowiedź!
2009-12-11T22:04:49+01:00
Zapisz w jak najprostszej postaci :
1.) (b+3)² - (b-3)² = b²+6b+9-b²+6b-9=12b
2.) (5m+4n)² - (4m-5n)² =25m²+40mn+16n²-16m²+40mn-25n²=9m²+80mn-9n²
3.) (3x-2)² + 2(x+3)² =9x²-12x+4+2(x²+6x+9)=9x²-12x+4+2x²+12x+18=
11x²+22
4.) (y²+1)² -2(y²-1)² =y⁴+2y²+1-2(y⁴-2y²+1)=y⁴+2y²+1-2y⁴+4y²-2=
-y⁴+6y²-1
5.) (5-0,2k³)² + 5(k³-5) =25-2k³+0,04k⁶+5k³-25=3k³+0,04k⁶

Jeśli zadowolona/y jesteś z rozwiązania,
to proś o pomoc i ...
kliknij na link:
http://zadane.pl/p/13585/madzia333
Pozdrawiam. Magda
1 5 1
2009-12-12T01:08:16+01:00
1)
(b + 3)² - (b - 3)² = b² + 6b + 9 - b² + 6b - 9 = 12b
2)
(5m + 4n)² - (4m - 5n)² = 25m² + 40mn + 16n² - 16m² + 40mn - 25n² = 9m² + 80mn - 9n²
3)
(3x - 2)² + 2(x + 3)² = 9x² - 12x + 4 + 2x² + 12x + 18 = 11x² + 22
4)
(y² + 1)² - 2(y² - 1)² = y⁴+ 2y² + 1 - 2y⁴+ 4y² - 2 = - y⁴+ 6y² - 1
5)
(5 - 0,2k³)² + 5(k³ - 5) = 25 - 2k³ + 0,04k⁶ + 5k³ - 25 = 0,04k⁶+ 3k³